2008
DOI: 10.1111/j.1469-7580.2008.00970.x
|View full text |Cite
|
Sign up to set email alerts
|

Microcephalia with mandibular and dental dysplasia in adult Zmpste24‐deficient mice

Abstract: ZMPSTE24 (also called FACE-1) is a zinc-metalloprotease involved in the post-translational processing of prelamin A to mature lamin A, a major component of the nuclear envelope. Mutations in the ZMPSTE24 gene or in that encoding its substrate prelamin A ( LMNA ) result in a series of human inherited diseases known collectively as laminopathies and showing regional or systemic manifestations (i.e. the Hutchinson-Gilford progeria syndrome). Typically, patients suffering some laminopathies show craniofacial or ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…(24) Murine cranial development has been used extensively to evaluate genetic impact on human cranial bone development, and 3D micro-CT has been assessed to validate the mouse cranium as a relevant model for clinical features of OI (25) and other genetic disorders. (26) Although Scl-Ab has been explored in many simulated disease models of low bone mass resulting from ovariectomy, (27,28) orchidectomy, (29) glucocorticoid exposure, (30) disuse, (31,32) spinal cord injury, (33) rotator cuff healing, (34) and fracture repair, (35,36) these studies and others were typically performed in mature animals where most cranial developmental processes are complete. Similarly, in studies of young OI mice, the effects of pharmacologic sclerostin inhibition on the cranium during periods of rapid growth and development have not yet been described.…”
Section: Introductionmentioning
confidence: 99%
“…(24) Murine cranial development has been used extensively to evaluate genetic impact on human cranial bone development, and 3D micro-CT has been assessed to validate the mouse cranium as a relevant model for clinical features of OI (25) and other genetic disorders. (26) Although Scl-Ab has been explored in many simulated disease models of low bone mass resulting from ovariectomy, (27,28) orchidectomy, (29) glucocorticoid exposure, (30) disuse, (31,32) spinal cord injury, (33) rotator cuff healing, (34) and fracture repair, (35,36) these studies and others were typically performed in mature animals where most cranial developmental processes are complete. Similarly, in studies of young OI mice, the effects of pharmacologic sclerostin inhibition on the cranium during periods of rapid growth and development have not yet been described.…”
Section: Introductionmentioning
confidence: 99%
“…Homozygous lmna HG/HG mice, that express progerin exclusively and no lamin A or C, displayed severe bone abnormalities, including spontaneous bone fractures in the extremities, poorly mineralized bones and premature death (21). In addition to skeletal abnormalities, Zmpste24-deficient mice also showed malformation of the teeth (15,22).…”
mentioning
confidence: 99%
“…Accordingly, Face-1/Zmpste24-deficient mice accumulate farnesylated prelamin A at the nuclear envelope and phenocopy human HGPS, providing a valuable animal model for the study of this pathology (Pendas et al 2002;Bergo et al 2002;Cadinanos et al 2005;de Carlos et al 2008). Using transcriptional profiling on tissues from this knockout model, we found that hyperactivation of p53 signalling plays a key role in the accelerated ageing phenotype, which is partially reversed by p53 deficiency .…”
Section: Introductionmentioning
confidence: 91%